Antiproliferative activity of various fractions from methanol extract of the leaves of muntingia calabura / Mohd Faiz Mustaffa - Mustaffa, Mohd Faiz (2009)
The World Health Organization (WHO) reported in 2007 that 7.9 million deaths worldwide (or 13% of total deaths) due to cancer, and the most common cancer in the world are lung, breast and colorectal cancer. 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay was used in the in vitro anticancer activity of Muntingia Calabura methanol extracts studies against MCF-7, HL60 and A549 cancer cell lines. M Calabura fresh leaves were air-dried approximately 2 weeks then soaked in methanol prior evaporated to dryness. The methanol crude partitioned sequentially in hexane, chloroform and methanol itself and subjected to anticancer activity. Methanol partition showed potent anticancer activity compare with others partition and methanol crude against MCF-7 (8.5 µg/mL), HL60 (3.2 µg/mL) A549 cancer cell (11 µg/mL). The potent activity of methanol partition towards both cancer cell lines was prior subjected to fractionation by using vacuum liquid chromatography (VLC). The fractions of methanol partition showed less potent against tested cancer cell line as compared to methanol partition itself exclude F5 and F6 tested on MCF-7 cancer cell line (5.5 and 7 µg/mL). Interestingly, all fractions failed to exert cytotoxic activities on cancer cell line especially on MCF-7, possessed cytotoxic activities on normal cell line, 3T3, which indicates the unsafe used of the fractions as chemotherapy. In conclusion, the extracts of M Calabura possess potential anticancer activity that requires further thorough studies.